The Joint Effect of Perceived Psychosocial Stress and Phthalate Exposure on Hormonal Concentrations during the Early Stage of Pregnancy: A Cross-Sectional Study - Henrieta Hlisníková; Miroslava Nagyová; Branislav Kolena; Miloš Mlynček; Tomáš Trnovec; Ida Petrovičová (MDPI AG, 2022)
Phthalates alter the hormonal balance in humans during pregnancy, potentially affecting embryonic and fetal development. We studied the joint effect of exposure to phthalates, quantified by urinary phthalate metabolite concentration, and perceived psychological stress on the concentration of hormones in pregnant women (n = 90) from the Nitra region, Slovakia, up to the 15th week of pregnancy. We used high-performance liquid chromatography, tandem mass spectrometry (HPLC-MS/MS), and electro-chemiluminescence immunoassay to determine urinary concentrations of phthalates and serum concentrations of hormones, respectively. We used Cohen perceived stress scale (PSS) to evaluate the human perception of stressful situations. Our results showed that mono(carboxy-methyl-heptyl) phthalate (cx-MiNP) and a molar sum of di-iso-nonyl phthalate metabolites (ΣDiNP) were negatively associated with luteinizing hormone (LH) (p ≤ 0.05). Mono(hydroxy-methyl-octyl) phthalate (OH-MiNP) and the molar sum of high-molecular-weight phthalate metabolites (ΣHMWP) were positively associated with estradiol (p ≤ 0.05). PSS score was not significantly associated with hormonal concentrations. When the interaction effects of PSS score and monoethyl phthalate (MEP), cx-MiNP, ΣDiNP, and ΣHMWP on LH were analyzed, the associations were positive (p ≤ 0.05). Our cross-sectional study highlights that joint psychosocial stress and xenobiotic-induced stress caused by phthalates are associated with modulated concentrations of reproductive hormones in pregnant women.